Komunikasi Pemasaran PT. Halal Network International Herba Penawar Alwahida Indonesia Dalam Meningkatkan Minat Beli Masyarakat - Nurhanifah Nurhanifah (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This study aims to analyze the Marketing Communication of PT. International Halal Network Alwahida Indonesian Herba Bidder (HNI HPAI) In Increasing People's Purchase Interest. The research method used is qualitative research. The data collection technique was carried out by interviewing, after which data analysis was carried out with the stages of reducing, categorizing the data, presenting the final data to draw conclusions. The results of this study found that BC 3 Medan HNI HPAI did not make marketing communication plans as mentioned in the marketing communication planning theory but they put forward real work rather than just plans. In the implementation of marketing communications carried out by BC 3 Medan HNI HPAI they did by holding events such as Home Sharing (HS), seminars on HNI HPAI, whether it contains motivation, introduction to companies and their products, to education about thibbunnabawi. During the implementation of marketing communications, of course the BC 3 HNI HPAI experienced obstacles. The obstacles they experience are of course the rejections that come from consumers and potential consumers. to increase this self-confidence, leaders can attend seminars held by HNI HPAI. The seminars that are held contain motivations that can inspire enthusiasm, as well as inspire the spirit and spirit of the leader himself.